2014
DOI: 10.1016/j.jecp.2014.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Using the axis of elongation to align shapes: Developmental changes between 18 and 24months of age

Abstract: An object’s axis of elongation serves as an important frame of reference for forming 3-dimensional representations of object shape. By several recent accounts, the formation of these representations is also related to experiences of acting on objects. Four experiments examined 18- to 24-month-old (N = 103) infants’ sensitivity to the elongated axis in action tasks that required extracting, comparing and physically rotating an object so that its major axis was aligned with that of a visual standard. In Experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(11 citation statements)
references
References 62 publications
2
9
0
Order By: Relevance
“…It may be that two year-olds work first with the axis of elongation for insertion problems; however, our data suggest that by two years of age, children can successfully align a second, shorter axis as well as an object with one axis. In Smith et al’s study [ 34 ], two year-olds took a maximum of three adjustments to align the long axis alone; two year-old participants in our study averaged less than three attempts to align the Bar shape and less than 5 to align the Cross shape and they were equally successful at aligning both objects.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…It may be that two year-olds work first with the axis of elongation for insertion problems; however, our data suggest that by two years of age, children can successfully align a second, shorter axis as well as an object with one axis. In Smith et al’s study [ 34 ], two year-olds took a maximum of three adjustments to align the long axis alone; two year-old participants in our study averaged less than three attempts to align the Bar shape and less than 5 to align the Cross shape and they were equally successful at aligning both objects.…”
Section: Discussionmentioning
confidence: 57%
“…The long axis of an object (the axis of elongation) develops as a key frame of reference for object perception and object action in the second year of life [ 34 ]. In Smith et al’s study [ 34 ], in the second experiment, when inserting objects downward into a rectangular cut-out [34 Experiment 2], two year-olds appeared to attend to the long axis regardless of whether they were inserting a simple object or a complex object. In Smith et al’s study [ 34 ], the task required aligning only the long axis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Others have shown that the characteristics of the body, the movements and the actions of babies are key in structuring the visual input and, therefore, constrain the perceptual experiences they can access (Bambach et al, 2016;Burnham, 1987Burnham, /2013Smith et al, 2011). Some pointed out, for instance, that aligning objects by their major axis improves markedly between 18 and 24 months depending on the interaction of children with objects (Smith et al, 2014). However, other studies suggest that the perception of other sensory dimensions such as surface glossiness would develop around 7 or distant object depends in no small extent on complex reasoning skills that babies do not have (Granrud, 2009(Granrud, , 2012.…”
Section: State Non-conceptualism and Its Problemsmentioning
confidence: 99%
“…Piaget documents an observation where his daughter makes an analogy between a doll's foot hooking her dress, and her own finger bent like a hook [14]. Tool use competence in humans emerges from explorative actions, such as those performed with the child's bare hands in the first year [15]. A longitudinal study on infants [10] shows that, at around 16-20 months, children start to intentionally and successfully bring faraway toys closer to themselves with the help of tools such as rakes.…”
Section: Related Workmentioning
confidence: 99%